Understanding and controlling condensation and frosting phenomena on engineered surfaces - Haque, Mohammad Rejaul (Kansas State University, 2019)
The significant advancement of micro/nano-structured surface engineering, demands the integration of material science with the heat transfer applications such as condensate harvesting, passive freezing, and frost formation etc. The energy and texture of the solid surface have significant effects on phase change phenomena. This phenomenon is also significantly influenced by environmental factors (temperature and humidity). At atmospheric pressure, a surface below the freezing point temperature for a given relative humidity nucleates water droplets heterogeneously on the surface, and subsequent freezing occurs resulting in frost formation which is a complex and fascinating phenomenon. Frequent defrosting is required to remove the ice that causes substantial economic losses. This work examines the combined effect of surface properties and environmental factors into the fundamental understanding of coalescence and pinning behavior in droplet growth mechanism, and freezing front propagation. Various nano-structured surfaces and engineered surfaces were fabricated to get the different surface energies and texture effects on droplet dynamics. After testing the wetting properties of every individual samples, condensation/freezing tests were conducted on the samples in humidity and temperature controlled chamber. The nanopillar surfaces had a significant effect on droplet dynamics via the pinning mechanism, and reduced the occurrences of coalescence events. Nanopillared surface accelerated freezing by order of magnitude compared to a plain hydrophilic surface at 60% RH. A mathematical model was developed for the pinning mechanism as a function of design parameters (pillar height, spacing, and radius) of the fabricated nanopillar surface. For the condensation test on graphene oxide (GO) coated copper surface, the pinning of droplets into the micro/nanostructures of the surfaces leads to the enhancement of condensate harvesting. The hydrophobic aluminum (Al-H), and hydrophobic graphene coated surface delays the freezing. The change in freezing kinetics, freezing time, the size of droplets at freezing, and the surface area covered at freezing, are all related to the rate of coalescence of droplets on the surface. Approximate ~6.78×, ~13.12× and ~17.32× freezing delay was observed at 269 K, 270 K, and 271 K surface temperatures respectively for the hydrophobic graphene surface compared to the plain silicon surface under same operating condition. The result promises the applicability of different engineered surfaces for significant energy savings in frost delaying, thermal management, and condensate harvesting applications.
Keywords: Condensation; Frosting; Droplet dynamics; Pinning mechanism; Coalescence; Engineered surfaces